Shadowing Femi(ni)cide, Madness and the Politics of Female Control in Louisa May Alcott's "A Whisper in the Dark" - Melodia Festa, Beatrice (Miscelánea: A Journal of English and American Studies, 2024)
The term ‘femicide’ entered public discourse only in the late 1970s, when feminist critic Diana Russell used the term to bring attention to male violence and discrimination against women. This article intends to re-examine therepresentation of femicide through Louisa May Alcott’s short story “A Whisper in the Dark” (1865) in light of studies on femicide and female violence. Drawing from Russell’s definition of femicide, its theoretical approach and multipleredefinitions, the article proceeds by exploring Alcott’s depiction of femicide in the text. After a preliminary discussion, I critically examine Alcott’s short storyin light of studies on femicide by placing the text within American female Gothic fiction. Afterwards, I will demonstrate how femicide in the tale is based upon aninterplay of three main tropes: wrongful confinement, the threshold and madness, all of which are themes that Alcott develops with astonishing topicality and which underscores the importance of the tale as an example of female abuseand domestic violence, a phenomenon that has improved considerably all over the world in recent years. I conclude by showing how Alcott illustrates the politics of female control and offers an example of femicide long before the term was ever used.
Keywords: femicide; Alcott; female abuse; madness; female control